The Euro area's macroeconomic balancing act - Guntram B. Wolff (Bruegel, 2011)
The European Systemic Risk Board (ESRB) and the proposed prevention and correction of macroeconomic imbalances regulation (EIP) are designed to avoid imbalances. However, these instruments overlap, and need clarification. Both the ESRB and the Commission, which is given certain powers by the EIP, must identify and act early on risks. Acting in the face of strong economic and political pressure is difficult. Complementing the current approach with transparent and rules-based mechanisms will reduce this problem. The EIP and ESRB can complement each other in terms of analysis and policy, and close collaboration will be vital. The EIP regulation can be used to ensure that ESRB recommendations are followed up. In the area of financial recommendations relevent to macroeconomic imbalances, the Commission should have a more formal requirement to act on ESRB recommendations. The EIP regulation would benefit from a clause allowing recommendations to be addressed not only to member states. Conflicts between the ESRB and Commission could arise. In this case, the Treaty requires the Commission to issue a recommendation even if the ESRB issues a negative finding. Legally, it might not be possible to exclude the use by the Commission of confidential information obtained in the ESRB.
Keywords: 330; EU-Politik; Gleichgewichtiges Wachstum; Finanzpolitik; EU-Staaten